Atmospheric carbon dioxide concentration as fuel gauge - Balázs M. Fekete (Scientific Reports)
Abstract Climate change skeptics like to point to the high atmospheric carbon dioxide concentration in paleo records as “proof” of the exaggeration of the climate change agenda. Instead of debunking these arguments, the present paper represents a thought experiment that considers the atmospheric carbon dioxide concentration in the past as a proxy for fossil fuel reserves and interprets the contemporary rise in carbon dioxide concentration as a fuel gauge to estimate the exhaustion of the remaining fossil fuel reserves under different energy consumption scenarios. The resulting conclusion is that the dangers of exhausting the remaining fossil fuel resources are likely on par with the anticipated adverse effects of climate change and should convince even climate change skeptics that the transition to non-fossil energy sources is inevitable and urgent since the remaining fossil fuel reserves will be likely exhausted in less than a century. The presented analysis goes further than the currently adopted “net-zero” ambitions. It demonstrates that there is no room for compromise and the transition has to be “true-zero” use of fossil fuels. Accounting gimmicks like carbon capture and sequestration or carbon trading are just as unsustainable as the continued reliance on fossil fuels.